Dual effects of radiotherapy on tumor microenvironment and its contribution towards the development of resistance to immunotherapy in gastrointestinal and thoracic cancers - Zhao, Deyao; Mo, Yingyi; Neganova, Margarita E.; Aleksandrova, Yulia; Tse, Edmund; Chubarev, Vladimir N.; Fan, Ruitai; Sukocheva, Olga A.; Liu, Junqi (Frontiers in Cell and Developmental Biology, 2023)
Successful clinical methods for tumor elimination include a combination of surgical resection, radiotherapy, and chemotherapy. Radiotherapy is one of the crucial components of the cancer treatment regimens which allow to extend patient life expectancy. Current cutting-edge radiotherapy research is focused on the identification of methods that should increase cancer cell sensitivity to radiation and activate anti-cancer immunity mechanisms. Radiation treatment activates various cells of the tumor microenvironment (TME) and impacts tumor growth, angiogenesis, and anti-cancer immunity. Radiotherapy was shown to regulate signaling and anti-cancer functions of various TME immune and vasculature cell components, including tumor-associated macrophages, dendritic cells, endothelial cells, cancer-associated fibroblasts (CAFs), natural killers, and other T cell subsets. Dual effects of radiation, including metastasis-promoting effects and activation of oxidative stress, have been detected, suggesting that radiotherapy triggers heterogeneous targets. In this review, we This is a provisional file, not the final typeset article OFFICIAL OFFICIAL critically discuss the activation of TME and angiogenesis during radiotherapy which is used to strengthen the effects of novel immunotherapy. Intracellular, genetic, and epigenetic mechanisms of signaling and clinical manipulations of immune responses and oxidative stress by radiotherapy are accented. Current findings indicate that radiotherapy should be considered as a supporting instrument for immunotherapy to limit the cancer-promoting effects of TME. To increase cancer-free survival rates, it is recommended to combine personalized radiation therapy methods with TME-targeting drugs, including immune checkpoint inhibitors.